Integration of cytokine and heterologous receptor signaling pathways - Bezbradica, J; Medzhitov, R (Springer Nature, 2009)
Cytokines are soluble mediators of cell communication that are critical in immune regulation. They induce specific gene-expression programs in responsive cells. Recent findings, however, indicate that cytokine receptors can regulate immune cell functions by transcription-independent mechanisms. Here we review the current understanding of how cytokine signaling regulates the functions of other signaling pathways by first discussing the 'traditional' transcription-mediated consequences of cytokine signaling and then providing a detailed description of transcription-independent lateral communications between cytokine receptors and other cellular receptors.